Progress in Active Ingredient Formulations. Issue 3 (1st July 2019) - Ashton, Mark D.; Hardy, John G.
The formulation and delivery of the biologically active ingredients (AIs) (for example, agrochemicals and active pharmaceutical ingredients (APIs)) is an inherently interdisciplinary area of research and development. In this short review we discuss the evolution of AI and API delivery systems towards smart stimuli-responsive formulations with precisely controlled delivery for specific applications. We also highlight a few examples of such systems using AIs from Johnson Matthey's controlled substance and API portfolio.